Development of small forms of farming in the agrarian sector of the economy - Yevhenii Lanchenko; Volodymyr Ivchenko (Економічний вісник університету, 2023)
Topicality. The production of labor-intensive agricultural products in the state is largely provided by small enterprises. They play an important role in food security, ensuring the employment of the rural population, and shaping the living environment in communities. Therefore, the research of the development of small forms of business in the agrarian sector of the economy during the period of war in Ukraine is relevant. Formulation of the problem. In the agrarian sector of the economy of Ukraine, the transformation of collective agricultural enterprises into market-type business entities took place. In large- and medium-sized agricultural enterprises, the concentration of production of less labor-intensive and export-oriented agricultural crops can be traced, and the number of employees in them continues to decrease. Therefore, determining the social and economic foundations of the development of small forms of business should be an important task of modern agrarian policy. The subject of research covers the theoretical and practical principles of the development of small forms of business in the agrarian sphere. The purpose of the work is to substantiate the social and economic directions of the development of small forms of business in the agrarian sector of the economy. Research methods: historical, systematic approach, abstract-logical, statistical-economic, calculation-constructive methods. Results of the work: the essence was summarized and the classification of types of small forms of management in the agrarian sector of the economy was carried out on the basis of organizational, legal and social and economic foundations of their development; the priority directions for the development of small forms of business to ensure employment and motivation of the rural population to formally conduct agribusiness are substantiated, taking into account their current economic condition; conceptual directions for improving the business economic activity of small businesses thanks to organizational and material support and infrastructural development of rural areas have been determined. Practical implementation: the formation of agrarian and regional policy at the macro- and meso-levels of the economy, the process of developing projects of state and local programs for the development of the agrarian sector of the economy and rural areas. Conclusions: organizational and financial and material support for the development of small forms of business in the agrarian sector of the economy will ensure a decrease in unemployment in the industry, will contribute to the development of the social and labor sphere in rural areas.